Human Rights in the Investigation Process of Death in Malaysia: A Reassessment (Kanun: Jurnal Undang-undang Malaysia, 2022)
Human rights are a right that is not only guaranteed by the Federal Constitution of Malaysia, but is also recognized at the international level. Article 2 of the European Convention on Human Rights (ECHR) has provided protection to an individual to enjoy life and interests as guaranteed by law. The enforcement of coroner’s law must always have the support of responsible parties, especially the government of a country, so that these fundamental rights are always implemented and preserved without any violation. Cases of death in custody, especially those involving misconduct or negligence by the police, prison and hospital, should be given special attention and investigated by the coroner thoroughly as they involve serious violations of human rights. Among the questions that should be considered is the ECHR as a model in a global perspective that outlines the guidelines for this inquest. The domestic legal framework regarding the inquest process needs to be refined with the application of fundamental rights principles that can be applied by coroners in Malaysia. This writing analyzes the application of Article 2 of the ECHR in the legal system of foreign jurisdictions, namely the United Kingdom and Australia, by studying the cases and developments of the latest legal provisions as an example to Malaysia so that coroners can perform their duties with full integrity in seeking the truth through death investigation or an effective and more systematic inquest.Keywords: Inquests, coroner, human rights, violation, death, criminal justiceFull text: PDF